Senam Nifas Memengaruhi Proses Involutio Uteri - Hastuti Usman; Artika Dewie; Muthmainnah Ahsan (Jurnal Bidan Cerdas, 2019)
Postpartum mothers are afraid to do many movements. If mothers do early ambulation, it can facilitate the process of uterine involution. This research is aim to clear out the effect of puerperal gymnastic on the uterine involution process to postpartum mothers. It uses a quasi-experiment design and Pretest and posttest control group design. The sampling technique uses an accidental sampling technique. The instrument in this study is the observation sheet, leaflet, andgymnastics guide.Statistical test using the Mann Whitney test. Before performing puerperal gymnastic, the average of the Fundal Height (Tinggi Fundus Uteri) of the intervention group was 10.9 cm, and the average of Fundal Height of the control group was 10.9 cm. The statistical test obtained p-value=0.457, which means there is no difference in the average the Fundal Height between the intervention group and the control group. Whereas after childbirth exercise, the average of Fundal Height of the intervention group was 0.9 cm, and the average of Fundal Height of the control group was 7.3 cm. Statistical test obtained p-value <0.001.To sum up, there is an effect of puerperal exercise on uterine involution speed. Suggestions for Puskesmas Kampung Baru, especially the midwives, are to provide postpartum gymnastics services for postpartum mothers to accelerate uterine involution.